2020
DOI: 10.1002/jpln.201900216
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of dissolved and particulate phosphorus via preferential flow pathways in a forest soil: An approach using zero‐tension lysimeters

Abstract: Phosphorus (P) fluxes from forest soils are not well understood. For temperate zone forests, there is some evidence from watershed studies that P export occurs mainly in preferential flow pathways during storm events after dry periods. Therefore, we tested the practical applicability of a sampling approach, which should allow for quantifying P concentrations and fluxes. We used zero‐tension lysimeters, which were installed beneath the topsoil and in the subsoil at plots in the Tharandt Forest (Saxony, East Ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 74 publications
3
19
0
Order By: Relevance
“…This nutrient flushing effect (Hornberger et al, 1994) has been describe also in other studies as a prominent feature of lateral export of nutrients; mainly N (DON) and C (DOC) (Qualls, G. Haines, 1991;van Verseveld et al, 2008;Weiler and Mcdonnell, 2006) but also P (DOP) (Burns et al, 1998;Missong et al, 2018a;Qualls et al, 2002;Sohrt et al, 2018). Makowski et al (2020), who measured P concentrations in vertical SSF, also reported nutrient-flushing in the first 2 hours of their sprinkling experiments.…”
Section: P Concentration Dynamics In Vertical and Lateral Ssfsupporting
confidence: 67%
See 3 more Smart Citations
“…This nutrient flushing effect (Hornberger et al, 1994) has been describe also in other studies as a prominent feature of lateral export of nutrients; mainly N (DON) and C (DOC) (Qualls, G. Haines, 1991;van Verseveld et al, 2008;Weiler and Mcdonnell, 2006) but also P (DOP) (Burns et al, 1998;Missong et al, 2018a;Qualls et al, 2002;Sohrt et al, 2018). Makowski et al (2020), who measured P concentrations in vertical SSF, also reported nutrient-flushing in the first 2 hours of their sprinkling experiments.…”
Section: P Concentration Dynamics In Vertical and Lateral Ssfsupporting
confidence: 67%
“…higher than at CON (230 g/m 2 ) and more than three times higher than at TUT (189 g/m 2 ). The only other study on P concentrations in vertical SSF, did not find a significant difference in Ptot concentrations of vertical SSF at 10 cm and 35 cm soil depth at their beech forest site in Saxony, Germany with Haplic Cambisol (Makowski et al, 2020).…”
Section: P Concentration Dynamics In Vertical and Lateral Ssfmentioning
confidence: 80%
See 2 more Smart Citations
“…From field studies like those described above and from lab experiments using soil columns, we know that the transport of P during high-intensity rainfall events occurs mainly along preferential flow paths (Cox et al, 2000;Fuchs et al, 2009;Julich et al, 2017b;Missong et al, 2018a). Preferential flow paths allow subsurface flow to bypass the soil matrix that otherwise has been shown to effectively retain P (Compton and Cole, 1998;Ilg et al, 2009;Johnson et al, 2016;Qualls et al, 2002).…”
Section: Introductionmentioning
confidence: 99%